2015
DOI: 10.15171/joddd.2015.015
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Accuracy of Four Age Estimation Methods Based on Panoramic Radiography of Developing Teeth

Abstract: Background and aims. Tooth development is widely used in determining age and state of maturity. Dental age is of high importance in forensic and pediatric dentistry and also orthodontic treatment planning .The aim of this study was to compare the accuracy of four radiographic age estimation methods.Materials and methods. Orthopantomographic images of 537 healthy children (age: 3.9-14.5 years old) were evaluated. Dental age of the subjects was determined through Demirjian’s, Willem’s, Cameriere’s, and Smith’s m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
2
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 38 publications
4
36
2
11
Order By: Relevance
“…Unlike the results of this pilot study, a study conducted in Iran concluded that Willem's method overestimated the age by 0.30 years in girls and 0.42 years in boys [27]. Similarly, Galić et al noted Willem's method to overestimate the age by 0.24 and 0.42 years, in girls and boys respectively [28].…”
Section: Year Of Birthcontrasting
confidence: 87%
“…Unlike the results of this pilot study, a study conducted in Iran concluded that Willem's method overestimated the age by 0.30 years in girls and 0.42 years in boys [27]. Similarly, Galić et al noted Willem's method to overestimate the age by 0.24 and 0.42 years, in girls and boys respectively [28].…”
Section: Year Of Birthcontrasting
confidence: 87%
“…Paired t-test revealed significant difference between mean chronologic age and dental age. 8 In our study, the mean of difference of estimated age by Cameriere’s method was 1.08 and by Demirjian’s method was 2.0 years. Our study also indicated an underestimation of age by Cameriere’s method, while overestimation of age by Demirjian’s method was noted only in four patients.…”
Section: Discussionsupporting
confidence: 42%
“…Another relevance of the radiological study is the use for the analysis of teeth with the purpose of determining the age of the deceased person, especially in the age group where dental development takes place, in the mineralization phase of the teeth 17 . This analysis allows determining the exact stage of development of the tooth germs, evidencing the rhizogenesis of the evaluated teeth.…”
Section: Resultsmentioning
confidence: 99%